FROM A MILITARY ACADEMY TO A DEFENCE UNIVERSITY: THE NEEDED TRANSFORMATION - Juhary, Jowati (European Scientific Journal, ESJ, 2012)
This paper analyses the journey of the Military Academy of Malaysia (MAM) and what it had achieved that led to the upgrade to become a defence university, the National Defence University of Malaysia (NDUM). As a young establishment, much of its aspirations and achievements are yet to be determined and analysed. The first part of this paper narrates the inception of the MAM in Malaysian higher learning education context. Focus is given on the need to have a tertiary military institution that reflects the national defence strategy and foreign policy. The second part of this paper concentrates on the achievements of the MAM and NDUM. This part too examines the significance of the upgrade from the academy to a defence university. Some implications and adjustments are discussed at the end of this paper since the new status is awarded to the youngest public university in Malaysia.